Desempeño docente de inglés en instituciones educativas secundarias públicas de Iquitos, 2021 según sexo - Armas Nolorbe, Luhana Paola (2023)
The objective of this research was to compare the performance of male and female English teachers in public secondary high schools in Iquitos 2021. This research is of a comparative type with field, contemporary transectional and univariate designs. The results show that male teachers obtained an average of 75,231 and female teachers 76,169 of a score transformed to 100, which places them in a category of competent teaching performance, but with a slightly better performance of female teachers. In the same way, it can be observed in the dimensions: preparation for student learning 72.857 < 78.734, teaching for student learning 73.043 < 76.346, participation of the school articulated to the community 72,600 < 75,409 and development of professionalism and teaching identity 73,571 < 76,190, To conclude, the Mann-Whitney U test shows that there is no significant difference in female and male teachers’ performance (Sig. Asymptotic = ,650 > α = 0.05).